Numbering all the bones - Rinaldi, Ann (Hyperion Paperbacks for Children, 2005)
Thirteen-year-old Eulinda, a house slave on a Georgia plantation in 1864, turns to Clara Barton, the eventual founder of the American Red Cross, for help in finding her brother Neddy who ran away to join the Northern war effort and is rumored to be at Andersonville Prison.